Sustainable entrepreneurship in Malaysia: a grounded theory / Profesor Madya Dr Amran Awang, AMP… [et al.] - Awang, Amran; Nik Abdul Rashid, Nik Ramli; Abdullah, Fader; Mohd Kassim, Kamsol; Nasirun, Noraini; Ismail, Ahmad; Shaari, Idrus; Amran, Shazwani (Institute of Research Management and Innovation (IRMI), 2015)
Argument posed in Shepherd and Patzelt (2011) of what is to be sustained? And what is to be developed? in capitalizing on sustainable entrepreneurship shall be explored further in Malaysia. Sustaining Malaysia with regard to her environment, community and entrepreneurship uphold her Vision 2020 in establishing herself as a developed country. The argument brought forward series of research questions to be explored. This research explores sustainable entrepreneurship in Malaysia based on those research questions, and other issues pertaining to developing country like Malaysia. Sustainable entrepreneurship should consider both what is to be sustained and what is to be developed simultaneously. Thus activities of nature preservation, life support and community shall enhance opportunity in production of services, products and processes beneficial economically and non-economically to individual, the economy and society (Shepherd & Patzelt, 2011). The study utilizes both qualitative and quantitative methods in capturing all elements mentioned under sustainable entrepreneurship definition. The qualitative method observes an inductive approach of focus group surveys at individual, organization and industry levels. The method capitalizes on Glaser and Strauss (1967) grounded theory approach where the theory is derived from the ground. The information will be used to formulate constructs that will form a model. On the other hand, the quantitative method shall put an effort in compiling the data to verify the model.